Thrombolysis in stroke patients with elevated inflammatory markers - Altersberger, Valerian L.; Enz, Lukas S.; Sibolt, Gerli; Hametner, Christian; Nannoni, Stefania; Heldner, Mirjam R.; Stolp, Jeffrey; Jovanovic, Dejana R.; Zini, Andrea; Pezzini, Alessandro; Wegener, Susanne; Cereda, Carlo W.; et al. (Journal of neurology, 2022)
Objective To investigate the prognostic value of white blood cell count (WBC) on functional outcome, mortality and bleeding risk in stroke patients treated with intravenous thrombolysis (IVT). Methods In this prospective multicenter study from the TRISP registry, we assessed the association between WBC on admission and 3-month poor outcome (modified Rankin Scale 3–6), mortality and occurrence of symptomatic intracranial hemorrhage (sICH; ECASS-II-criteria) in IVT-treated stroke patients. WBC was used as continuous and categorical variable distinguishing leukocytosis (WBC > 10 × 10 9 /l) and leukopenia (WBC < 4 × 10 9 /l). We calculated unadjusted/ adjusted odds ratios with 95% confidence intervals (OR [95% CI]) with logistic regression models. In a subgroup, we analyzed the association of combined leukocytosis and elevated C-reactive protein (CRP > 10 mg/l) on outcomes. Results Of 10,813 IVT-treated patients, 2527 had leukocytosis, 112 leukopenia and 8174 normal WBC. Increasing WBC (by 1 × 10 9 /l) predicted poor outcome (OR adjusted 1.04[1.02–1.06]) but not mortality and sICH. Leukocytosis was independently associated with poor outcome (OR adjusted 1.48[1.29–1.69]) and mortality (OR adjusted 1.60[1.35–1.89]) but not with sICH (OR adjusted 1.17[0.94–1.45]). Leukopenia did not predict any outcome. In a subgroup, combined leukocytosis and elevated CRP had the strongest association with poor outcome (OR adjusted 2.26[1.76–2.91]) and mortality (OR adjusted 2.43[1.86–3.16]) when compared to combined normal WBC and CRP. Conclusion In IVT-treated patients, leukocytosis independently predicted poor functional outcome and death. Bleeding complications after IVT were not independently associated with leukocytosis.